Promotion through social media platform marketing: evaluating the ethical role of social media influencers in Sri Lanka’s 2024 political campaigns - Shivany, S.; Kumarasinghe, K.H.A.N. (Taylor and Francis Publication, 2026)
This qualitative study examines the role of influencer marketing in political campaigns during Sri Lanka’s 2024 presidential election, focusing on the impact of social media on voter perceptions and engagement. As political discourse increasingly shifts to digital platforms, influencers have emerged as central figures in shaping political narratives. The study adopted snowball sampling to collect data through semi-structured interviews and focus group discussions, involving 10 social media influencers and 50 voters. Thematic analysis revealed five key themes: voter trust, voter engagement, the impact of influencers, ethical dilemmas, and the overall role of influencers. The findings suggest that influencers are viewed as credible and relatable sources of information, especially among younger voters who are more engaged with digital campaigns that effectively leveraged influencers, experienced improved visibility and a stronger connection with their target audience. The investigation also revealed challenges such as spreading misinformation and concerns regarding the authenticity of influencer endorsements. Participants emphasized the need for transparency in influencer partnerships to maintain trust in political messaging. Ultimately, this study provides valuable insights into the intersection of social media and political marketing, offering a foundation for future research on digital engagement in political contexts within Sri Lanka and beyond.